An adaptive control scheme for articulatory synthesis of plosive-vowel sequences - Huang, Guangpu (2013)
We present an adaptive control scheme in a neural based model to improve the performance of articulatory based speech synthesis. The model generates the articulatory trajectories for English plosive-vowel patterns through regional target approximation in the articulatory domain and categorical perception in the auditory domain. The proposed method can effectively model the variations of static vowel sounds and adapt to changes and uncertainties in the dynamic plosive sounds. Simulation studies demonstrate that the proposed scheme is able to estimate and regulate the control parameters in the articulatory synthesizer to produce smooth and authentic acoustic phonetic output.